Analisis Pengaruh Jumlah Tenaga Kerja, Besarnya Net Ekspor, dan Besarnya Konsumsi Terhadap PDRB: Studi Provinsi Di Indonesia - Tajul 'Ula; Dhiyaul Fayyadh (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2023)
Economic globalization provides opportunities and risks to economic growth in Indonesia. This study aims to analyze the effect of the number of workers, net exports and household consumption on the GRDP of the provinces in Indonesia. This study uses the Fixed Effect Model (FEM) panel data analysis model using the variables GRDP, percentage of labour, total net exports, and household consumption for each province in Indonesia in 2015-2020. The results showed that household consumption and exports contributed positively to the GRDP for each province, although in small amounts. Meanwhile, the workforce has not contributed to economic growth. Therefore, it is recommended for each region to increase cooperation in increasing development and increasing investment in the field of export commodities so that there is an increase in export volume, which has a positive impact on economic growth. The policy of creating jobs through increased investment needs to be carried out to reduce unemployment and affect economic growth